Chirality transfer of cysteine to the plasmonic resonance region through silver coating of gold nanobipyramids. Issue 26 (1st March 2021) - Wang, Ye; He, Wei; Li, Chun Hong; Xia, Chang; Yan, Yuan; Li, Chun Mei; Huang, Cheng Zhi
Abstract : We report a chirality transfer of cysteine to the plasmonic resonance region, which was significant for understanding the role of cysteine and the mechanism in controlling the chirality of designed nanoparticles. Abstract : Here we report a chirality transfer of cysteine, which at first was to the plasmonic resonance region of gold nanobipyramids and then to that of Ag nanoshells with increasing growth of Ag layers, owing to the important role of the free Cys embedded within the Ag nanoshell. Our finding is helpful for developing new chiral plasmonic nanomaterials with the best designed asymmetric properties.